2009
DOI: 10.1177/193229680900300528
|View full text |Cite
|
Sign up to set email alerts
|

Delays in Minimally Invasive Continuous Glucose Monitoring Devices: A Review of Current Technology

Abstract: Through the use of enzymatic sensors—inserted subcutaneously in the abdomen or ex vivo by means of microdialysis fluid extraction—real-time minimally invasive continuous glucose monitoring (CGM) devices estimate blood glucose by measuring a patient's interstitial fluid (ISF) glucose concentration. Signals acquired from the interstitial space are subsequently calibrated with capillary blood glucose samples, a method that has raised certain questions regarding the effects of physiological time lags and of the du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
138
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(147 citation statements)
references
References 25 publications
6
138
0
3
Order By: Relevance
“…20,21 Such time delays are caused by two factors: (1) a physiological delay between changes in BG and interstitial glucose and (2) device-dependent delays in measurement. 20,22 In this evaluation, the MARD and the PARD were remarkably better during induced glucose fluctuations compared with available CGM systems. 6,16 This suggests a decreased device-dependent time delay, as the physiological delay is assumed to be constant/comparable among CGM systems.…”
Section: Discussionmentioning
confidence: 93%
“…20,21 Such time delays are caused by two factors: (1) a physiological delay between changes in BG and interstitial glucose and (2) device-dependent delays in measurement. 20,22 In this evaluation, the MARD and the PARD were remarkably better during induced glucose fluctuations compared with available CGM systems. 6,16 This suggests a decreased device-dependent time delay, as the physiological delay is assumed to be constant/comparable among CGM systems.…”
Section: Discussionmentioning
confidence: 93%
“…The reported time lag between glucose changes in both compartments is about 5 to 25 minutes. 4,6,[8][9][10] This range of time lag can be explained by the fact that the gradient in glucose increase in blood differs depending on the type and amount of carbohydrates in a given meal; that is, the increase in glycemia is steeper with a high glucose load and rapidly absorbable carbohydrates. Differences in prandial glucose profiles between blood and ISF most likely also depend on the glucose utilization rate in the given compartment: If the glycogen storage capacity in the liver is different in a given patient on different days, this might have an impact on how rapidly glucose is taken up by this organ and subsequently how rapidly ISF glucose levels decline.…”
Section: Entity 3: Meal-related Glucose Differences Between Bg and Isfmentioning
confidence: 99%
“…6 The calibration of the ISF signal to BG by means of capillary BG measurements may have an impact on the maximal glucose levels recorded.…”
Section: Relevance Of Measuring Glucose In Two Different Compartmentsmentioning
confidence: 99%
“…19 Further improvements in accuracy may be achievable through the intravenous sampling route eliminating or significantly reducing the lag time of 6-15 min reported with subcutaneous sensors. 13,[20][21][22] Preliminary studies using the intravenous microdialysis technique have shown high accuracy (mean absolute relative deviation, 5.6%; data points in Clarke error grid Zone A, 97%). 23 Advantages of subcutaneous glucose monitoring compared with intravenous measurements include reduced invasiveness obviating the need for dedicated venous placement and a risk of contamination from dextrose or other medications that may interfere with glucose measurements.…”
Section: Discussionmentioning
confidence: 99%